Emergence of core–peripheries in networks - T. Verma (Nature Portfolio, 2016)
Many transport networks exhibit a core–periphery structure, where few nodes are highly interconnected and the rest form a tree-shaped structure. Here, the authors demonstrate how to generate such a structure through a pruning process based on removal of underutilized links and redistribution of loads.